The Effect of Dark Leadership Perception on Quiet Quitting and The Mediating Role of Presenteeism: A Study on Healthcare Workers - Çırak, Melike; Esen, Murat (International Journal of Contemporary Economics and Administrative Sciences, 2025)
This study investigates the effect of dark leadership perception on quiet quitting and the mediating role of presenteeism (failure to work engagement) among healthcare employees. While dark leadership has gained attention in recent literature as a critical leadership issue, previous research lacks empirical evidence examining the proposed model that integrates dark leadership perception with presenteeism and quiet quitting. Thus, this study bridges a critical gap in the literature by empirically demonstrating how dark leadership perception triggers quiet quitting through the mediating role of presenteeism. Using a sample of 560 healthcare workers from public hospitals in Izmir, Türkiye, data were collected by questionnaires and analyzed through SPSS 25.0 and AMOS. Data analysis included descriptive statistics, reliability analysis, exploratory and confirmatory factor analysis, and structural equation modeling. The results reveal that dark leadership significantly increases both quiet quitting and presenteeism. Furthermore, presenteeism amplifies quiet quitting behaviors and fully mediates the relationship between dark leadership perception and quiet quitting. These findings contribute to the literature by introducing a novel perspective on how dark leadership behaviors propagate counterproductive employee outcomes through psychological disengagement. The study underscores the urgency of addressing dark leadership in healthcare settings to mitigate workforce attrition and productivity loss.